Colonising myths-Maori realities: He rukuruku whakaaro - Mikaere, Ani (Huia Publishers, 2011)

New treaty, new tradition: reconciling New Zealand and Maori law - Jones, Carwyn (UBC Press, 2016)

The Treaty on the ground : where we are headed, and why it matters - Bell, Rachael; Kāwharu, Margaret; Taylor, Kerry; Belgrave, Michael; Meihana, Peter (Massey University Press, 2017)
"The coalface reality of honouring the Treaty of Waitangi in today's law, local government, education, health, social services and more"–Cover.
Keywords: Mana whakahaere; Māori (New Zealand people) – Government relations; New Zealand – Race relations; New Zealand – Social conditions – 21st century; Tiriti o Waitangi; Treaty of Waitangi (1840 February 6)

Māori and the environment: kaitiaki - Selby, Rachael; Moore, Pataka J. G.; Mulholland, Malcolm; Te Wānanga-o-Raukawa (Huia, 2010)
Keywords: Taiao; citizen participation; environmental policy; environmental protection; kaitiakitanga; new zealand; social life and customs; tūkinotanga ā taiao; water conservation

Ka takahia ano o tātou tapuae = retracing our steps: a Māori governance overview and literature review - Fodder, Torivio A.; Davis-Ngatai, Priscilla; Joseph, Robert (Te Mata Hautū Taketake - The Māori & Indigenous Governance Centre, University of Waikato, 2014)
Keywords: governance; rangahau māori; tikanga | indigenous law

Parekura Horomia: 'Kia ora, chief!' - Gardiner, Wira (Huia Publishers, 2014)
Keywords: government; labour party; memoir; māori politicians; politicians

Standing for Mana - Cleave, Peter (Campus Press, 2012)
Keywords: elections; government; government relations; kāwanatanga; mana party; parliament; political activity

Point of Order Mr Speaker: Modern Māori Political Leaders - Katene, Selwyn; Katene, Rahui (Huia NZ Ltd, 2017)
Eight current or former Maori politicians from different political parties recount their leadership experiences, and describe the significant events in their journeys from their early lives to Parliament. Paula Bennett, Te Ururoa Flavell, Hone Harawira, Tau Henare, Shane Jones, Nanaia Mahuta, Hekia Parata and Metiria Turei give readers a unique glimpse into their personal and public lives. They share their dreams and aspirations, lessons learned and knowledge gained while making meaningful contributions to Maori development.
Keywords: government; kāwanatanga; leadership; māori politicians; politicians

Panguru and the city: kāinga tahi, kāinga rua : an urban migration history - Williams, Melissa Matutina (Bridget Williams Books, 2015)
Keywords: history; social conditions; social networks; te rarawa; urbanisation

Poata: seeing beyond the horizon : a memoir - Poata, Tama (Steele Roberts, 2012)
Keywords: activism; government; human rights workers; kōrero nehe; kōrero taumata; land march; memoir; protest; springbok tour protests; tino rangatiratanga; tiriti o waitangi/treaty of waitangi

Making our place: exploring land-use tensions in Aotearoa New Zealand - Ruru, Jacinta; Abbott, Mick; Stephenson, Janet (Otago University Press, 2011)
Keywords: colonisation; economic aspects; environment; land tenure; land use; social aspects; treaty negotiations

Tupuna Awa: People and Politics of the Waikato River - Muru-Lanning, Marama (Auckland University Press, 2016)
'We have always owned the water . . . we have never ceded our mana over the river to anyone', King Tuheitia Paki asserted in 2012. Prime Minister John Key disagreed: ‘King Tuheitia's claim that Maori have always owned New Zealand's water is just plain wrong'. So who does own the water in New Zealand – if anyone – and why does it matter? Offering some human context around that fraught question, Tupuna Awa looks at the people and politics of the Waikato River. For iwi and hapu of the lands that border its 425-kilometre length, the Waikato River is an ancestor, a taonga and a source of mauri, lying at the heart of identity and chiefly power. It is also subject to governing oversight by the Crown and intersected by hydro-stations managed by state-owned power companies: a situation rife with complexity and subject to shifting and subtle power dynamics. Marama Muru-Lanning explains how Maori of the region, the Crown and Mighty River Power have talked about the ownership, guardianship and stakeholders of the river. By examining the debates over water in one New Zealand river, over a single recent period, Muru-Lanning provides a powerful lens through which to view modern iwi politics, debates over water ownership, and contests for power between Maori and the state.
Keywords: iwi politics; water ownership

The changing role of the leader in Māori society: a study in social change and race relations - Winiata, Maharaia (University of Waikato, 2014)
Keywords: government; government relations; iwi politics; kāwanatanga; kōrero nehe; leadership; noho-ā-iwi; pre-colonisation; race relations; rangatira; rangatiratanga; social life and customs

Conversations about indigenous rights: the UN Declaration on the Rights of Indigenous Peoples and Aotearoa New Zealand - Katene, Selwyn; Taonui, Rawiri (Massey University Press, 2018)
The UN declaration on the Rights of Indigenous Peoples is a deeply significant document. In 2007, then UN Secretary-General Ban Ki-moon described its signing as an "historic moment when UN Member States and indigenous peoples reconciled with their painful histories and resolved to move forward together on the path of human rights, justice and development for all". This book reflects on the tenth anniversary of the UN General Assembly's adoption of the Declaration and examines its relevance in New Zealand. It shows the strong alignment between the Treaty of Waitangi and the Declaration, and examines how the Declaration assists the interpretation and application of Treaty principles of partnership, protection and participation. Starting from a range of viewpoints and disciplines, the authors agree that in Aotearoa New Zealand the journey to full implementation is now well underway, but warn that greater political leadership, willpower, resources and a stronger government commitment is needed.
Keywords: UNDRIP; civil Rights; international relations; print only; tikanga | indigenous law; tiriti o waitangi/treaty of waitangi

New myths and old politics: the Waitangi Tribunal and the challenge of tradition - O'Regan, Tipene (Bridget Williams Books, 2015)
"Negotiating a claim before the Waitangi Tribunal can involve troubling challenges to an iwi's legitimacy, sometimes from unexpected places. In this unique behind-the-scenes account of the negotiation of Ngāi Tahu's Waitangi Tribunal claim, Sir Tipene O'Regan describes what happened when claims of New Age mysticism attempted to undermine traditional whakapapa and academic scholarship"–Publisher information.
Keywords: iwi politics; kāi tahu; tiriti o waitangi/treaty of waitangi; treaty claims; waitangi tribunal; whakapapa; whenua

Water rights for Ngāi Tahu: a discussion paper - Tau, Te Maire (Canterbury University Press, 2017)
"There is perhaps no issue in New Zealand today more contentious than water rights. The Crown claims that no one owns water, but its use, irrigation and treatment are controlled by local governments empowered by the Crown. Since the 1990s resource consents for the taking of water, in Canterbury and Southland especially, have increased dramatically and the environmental situation is reaching a breaking point. After years of discussion some kind of system regarding the ownership of water is inevitable. In Water Rights for Ngāi Tahu, Te Maire Tau considers the historical and political framework that has contributed to the current state of water rights in the Ngāi Tahu takiwā. He explores the customary, legal and Treaty frameworks that feed into the debate regarding the ownership of water. From 1844 to 1864 the Crown purchased more than 34.5 million acres of land from Ngāi Tahu, but in most purchase deeds water is not mentioned. How does this play into claims to water? Should the Treaty be relied upon? How far can kaitiakitanga take us if the goal is mana motuhake and tino rangatiratanga? In this short book Te Maire Tau lays out the historical background and context to water rights, and opens a discussion about where to proceed next in determining a Ngāi Tahu position on water."–Back cover.
Keywords: kāi tahu; law; legislation; natural resources; resource management act 1991; tiriti o waitangi/treaty of waitangi; treaty claims; ture putaiao; water rights

Indigenous Data Sovereignty: Toward an agenda - Kukutai, Tahu (ANU Press, 2016)
As the global ‘data revolution’ accelerates, how can the data rights and interests of indigenous peoples be secured? Premised on the United Nations Declaration on the Rights of Indigenous Peoples, this book argues that indigenous peoples have inherent and inalienable rights relating to the collection, ownership and application of data about them, and about their lifeways and territories. As the first book to focus on indigenous data sovereignty, it asks: what does data sovereignty mean for indigenous peoples, and how is it being used in their pursuit of self-determination? The varied group of mostly indigenous contributors theorise and conceptualise this fast-emerging field and present case studies that illustrate the challenges and opportunities involved. These range from indigenous communities grappling with issues of identity, governance and development, to national governments and NGOs seeking to formulate a response to indigenous demands for data ownership. While the book is focused on the CANZUS states of Canada, Australia, Aotearoa/New Zealand and the United States, much of the content and discussion will be of interest and practical value to a broader global audience.
Keywords: data; data sovereignty; indigenous data sovereignty

Here to stay: Reshaping the regions through mana Māori - Kukutai, Tahu; Simmonds, Naomi Beth; Ryks, John (Massey University Press, 2016)
Situated 65 kilometres south-east of Hamilton, Putāruru (population 3747 in the 2013 Census) is typical of the many farming service towns scattered across rural Aotearoa New Zealand. Bakeries, op shops, a sports bar and a farm equipment supplier occupy the main street. Unlike nearby Tirau, which transformed from a one-stop shop into a vibrant boutique village in the late 1990s, Putāruru township remains largely indistinguishable from other rural centres. There are few clues to the substantial farming-based and water-generated wealth that lies beyond the town.
Keywords: economic aspects; mana whenua; tino rangatiratanga

The State of Māori rights - Mutu, Margaret (Huia, 2015)
The State of Maori Rights brings together a set of articles written between 1994 and 2009. It places on record the Maori view of events and issues that took place over these years, issues that have been more typically reported to the general public from a 'mainstream' media perspective. It is an important documentation of these fifteen years of New Zealand history, recording the assertion of Maori rights as the indigenous people of Aotearoa New Zealand, focusing on Maori issues and experiences and written from a Maori perspective.
Keywords: civil Rights; colonisation; crown violence; foreshore and seabed act 2004; government relations; intergenerational trauma; kāwanatanga; mana motuhake; māori electorates; māori rights; race relations; racism; te pāti māori; tiriti o waitangi/treaty of waitangi; voting; waitangi tribunal

Ngāti Kahu: portrait of a sovereign nation: history, traditions and Tiriti o Waitangi claims / Kia pūmau tonu te mana motuhake o ngā hapū o Ngāti Kahu - Mutu, Margaret; Pōpata, Lloyd; Williams, Te Kani; Herbert-Graves, Ānahera; Rēnata, Reremoana; Cooze, JudyAnn; Pineaha, Zarrah; Thomas, Tania; Kingi-Waiaua, Te Ikanui; Te Rūnanga-a-Iwi o Ngāti Kahu; Wackrow Williams and Davies Ltd (Huia Publishers, 2017)
"This book describes the iwi of Ngāti Kahu through the traditions and histories of each of the sixteen hapū, told by kuia and kaumātua and kept alive for future generations. These include histories of poverty, deprivation and marginalisation at the hands of the Crown, and loss of lands of the iwi. The book examines the range of techniques used by the Crown to justify its actions and the way these laid the groundwork for continuing injustices. The remedies needed to redress these injustices and achieve reconciliation of Ngāti Kahu and the Crown are set out. These include constitutional change to achieve the restoration of political, social and economic well-being to Ngāti Kahu, Crown relinquishment of all Ngāti Kahu lands to their rightful owners and payment of sufficient compensation to ensure no further Treaty of Waitangi claims. This history of Ngāti Kahu details the range of Crown actions against Ngāti Kahu to the current day, the effects of these actions on the people of Ngāti Kahu and the concerted and continuing efforts by Ngāti Kahu for remedies and reconciliation with the Crown"–Publisher information.
Keywords: colonisation; constitutional transformation; government relations; hapū; history; kāwanatanga; kōrero nehe; mana motuhake; ngāti kahu; noho-ā-iwi; tino rangatiratanga; tiriti o waitangi/treaty of waitangi; treaty claims; tūpuna

International indigenous rights in Aotearoa New Zealand - Erueti, Andrew (Victoria University Press, 2017)
Over the past four decades, international indigenous rights have become a prominent aspect of international law and are now enshrined in the UN Declaration on the Rights of Indigenous Peoples. Yet, while endorsed by Aotearoa New Zealand in 2010, little remains known about how these standards came about, how the international movement that created them was established, and the implications of these standards on national reforms already protecting Māori rights. International Indigenous Rights in Aotearoa New Zealand seeks to answer these questions. This collection of essays places the Declaration in the context of New Zealand rights around such issues as Treaty settlements, mining policy and the status of Māori children. Crucially, it also asks how Māori can hold New Zealand to account against international indigenous rights.
Keywords: UNDRIP; government relations; human rights; iwi taketake; law; self-determination; tikanga | indigenous law; tiriti o waitangi/treaty of waitangi; treaty claims

Ko te whenua te utu = Land is the price essays on Maori history, land and politics. - Sorrenson, M. P. K. (Auckland University Press, 2014)
For more than half a century, Keith Sorrenson - one of New Zealand's leading historians and himself of mixed Maori and Pakeha descent - has dived deeper than anyone into the story of two peoples in New Zealand. In this new book, Sorrenson brings together his major writing from the last 56 years into a powerful whole, covering topics from the origins of Maori (and Pakeha ideas about those origins), through land purchases and the King Movement of the nineteenth century, and on to twentieth-century politics and the new history of the Waitangi Tribunal.
Keywords: colonisation; history; kīngitanga; kōrero nehe; land tenure; tiriti o waitangi/treaty of waitangi; waitangi tribunal

Maori and Parliament: Diverse Strategies and Compromises - Bargh, Maria (Huia Publishers, 2010)
New Zealand is at a watershed in its constitutional and political arrangements. There are three events looming in the short term which suggest that the status of Māori in Parliament is in for significant challenge.The first is the impending review of constitutional issues and the Māori seats as part of the National Party–Māori Party ‘Relationship and Confidence and Supply Agreement’.Secondly, the proposed referendum on the future of the mixed member proportional system (MMP) could also have significant implications for Māori.Finally, the longer term question of whether New Zealand should become a republic continues to haunt New Zealand’s political imagination, and would also necessitate lengthy debates about the place of New Zealand’s constitutional arrangements in relation to Māori rights and Te Tiriti o Waitangi.Māori and Parliament provides a comprehensive and enlightening context for understanding both the historical and contemporary relationship between Māori and Parliament and highlights many of the issues which would arise in any discussion of New Zealand constitutional reform.Māori and Parliament is a collection of nineteen presentations and papers from twenty-one academics, political commentators and current and former parliamentarians and is the result of the Māori and Parliament conference held at Parliament in May 2009.Contributors include Georgina Beyer, Hon. Simon Bridges, Damian Edwards, Te Ururoa Flavell, Dr Janine Hayward, Colin James, Shane Jones, Basil Keane, Hon. Sir Douglas Kidd, Professor Steven Levine, Sir Ngatata Love, Hon. Nanaia Mahuta, Sir Tipene O’Regan, Professor Nigel Roberts, Prof. Ann Sullivan, Metiria Turei, Hon. Tariana Turia, Dr Charlotte Williams, Dr John Wilson, Prof. Whatarangi Winiata and Dr Maria Bargh.
Keywords: kāwanatanga; legislative; māori politicians; māori seats; parliament; political parties

The neoliberal state, recognition and indigenous rights: new paternalism to new imaginings - Bargh, Maria; Howard-Wagner, Deirdre; Altamirano-Jiménez, Isabel (Austrlian National University, 2018)
Keywords: civil Rights; crown law; crown policy; tikanga | indigenous law

Scaling up education reform: addressing the politics of disparity - Bishop, Russell (NZCER Press, 2010)
Keywords: education; educational change; mātauranga māori

Indigeneity: a politics of potential: Australia, Fiji and New Zealand - O'Sullivan, Dominic (Policy Press, 2017)
Keywords: australia; citizenship; government; kāwanatanga; rangatiratanga

Māori identity and economic wellbeing - Houkamau, Carla (Routledge, 2019)
This chapter considers the link between ethnicity and economic wellbeing for the Māori of New Zealand. In the context of 175 years of colonization, identity and culture remain an important determinant of Māori people’s economic wellbeing. Drawing from diverse strands of literature, the chapter considers the relationship between identity, culture and economic practices for Māori. Empirical research related to Māori identity and economic preferences will be discussed, including a discussion of the link between cultural dimensions (collectivism/individualism) and Māori economic practices. Specific outcomes will be related to different sub-groups of Māori; including a discussion of the impacts of discrimination on Māori who are sole identifiers (i.e. two Māori parents) as opposed to mixed Māori/European. The positive impacts of enculturation for Māori subjective wellbeing will be outlined. Policy implications are also reviewed, particularly suggestions on how to develop appropriately tailored programmes which meet the cultural needs of Māori people.
Keywords: identity

Always Speaking: The Treaty of Waitangi and Public Policy - Tawhai, Veronica; Gray-Sharp, Katarina (Huia Publishers, 2011)
This is a collection of papers that examine the current place of the Treaty of Waitangi in core public policy areas. The authors analyse the tensions and dynamics in the relationship between Maori and the Crown in their areas of expertise, detail the key challenges being faced, and provide insights on how these can be overcome. The policy areas covered in the collection span the environment, Maori and social development, health, broadcasting, the Maori language, prison and the courts, local government, research, science and technology, culture and heritage, foreign affairs, women's issues, labour, youth, education, economics, housing and the electoral system.
Keywords: civil Rights

Weeping Waters: The Treaty of Waitangi and Constitutional Change - Mulholland, Malcolm; Tawhai, Veronica (Huia Publishers, 2010)
Weeping Waters is a must read for anyone who wants to be informed about the current debate regarding the Treaty of Waitangi and a constitution for Aotearoa New Zealand. The book features essays from eighteen well-known and respected Maori figures including Professor Margaret Mutu, Bishop Muru Walters, Judge Caren Fox and lawyer Moana Jackson. This is the first book in recent years to offer a M?ori opinion on the subject of constitutional change. It shows how M?ori views have been ignored by successive governments and the courts and how M?ori have attempted to address constitutional issues in the past. The book also provides suggestions for a pathway forward if the Treaty of Waitangi is to be fully acknowledged as the foundation for a constitution for Aotearoa New Zealand.
Keywords: constitution; history; māori views

Indigenous Peoples and Demography: The Complex Relation between Identity and Statistics - Chapter 2 Building ethnic boundaries in New Zealand; representations of Maori identity in the census - Kukutai, Tahu (Berghahn Books, 2011)
When researchers want to study indigenous populations they are dependent upon the highly variable way in which states or territories enumerate, categorise and differentiate indigenous people. In this volume, anthropologists, historians, demographers and sociologists have come together for the first time to examine the historical and contemporary construct of indigenous people in a number of fascinating geographical contexts around the world, including Canada, the United States, Colombia, Russia, Scandinavia, the Balkans and Australia. Using historical and demographical evidence, the contributors explore the creation and validity of categories for enumerating indigenous populations, the use and misuse of ethnic markers, micro-demographic investigations, and demographic databases, and thereby show how the situation varies substantially between countries.
Keywords: anthropology; census; crown policy; ethnic identity

Good data practices for indigenous data sovereignty and governance - Lovett, Raymond; Lee, Vanessa; Kukutai, Tahu; Cormack, Donna; Rainie, Stephanie; Walker, Jennifer (Institute of Network Cultures, 2019)
Indigenous Data Sovereignty (IDS) and Indigenous Data Governance (IDG) art terms increasingly being used across community, research, policy and in practice. The IDS movement has emerged in response to poor data practices, from the conceptualisation of data items through to reporting of data about Indigenous peoples. This chapter aims to provide clarity concerning the definitions of IDS and IDG; provide an overview of the historical context in which IDS has emerged; and provide examples of IDS and IDG across the spectrum of community, policy and practice.
Keywords: data; data sovereignty; statistics